EP1155 Endoscopic near infrared and indocyanine green to verify the viability of the subcutaneous flap for vulvar cancer. (1st November 2019) - Capozzi, VA; Pugliese, M; Cianciolo, A; Gambino, G; Sozzi, G; Armano, G; Monfardini, L; Gaiano, M; Ceni, V; Rolla, M; Merisio, C; Berretta, R
Abstract : Introduction/Background: Vulvar cancer often requires radical vulvectomy with subsequent vulvar flap due to tumor aggressiveness and a high percentage of relapses. Approximately in 20–60% of cases, there are post-operative complications ranging from infection to wound dehiscence, lymphocele and flap necrosis that often require reoperation. Several methods have been described to verify the vitality of the flap, especially in plastic surgery, but these are often expensive and require specific machinery that is not generally present in a gynecological clinic. We present a viability verification of V-Y fasciocutaneous advancement flap for vulvar reconstruction by Endoscopic Near-Infrared and Indocyanine Green. Methodology: The patient was a 67-year-old woman with FIGO IB ≤ 4 cm squamous cell vulvar cancer with the absence of inguinal lymphadenopathy. The lesion appeared about 35 mm from the lateral margin of the large left lip and extended to the left inguinocrural fold (figure 1 ). The patient underwent left inguinal lymphadenectomy and left radical hemivulvectomy with a left fasciocutaneous medial-thigh advancement flap. For the evaluation of the flap, we endovenous administered 50 mg of Indocyanine Green diluted in 10 ml of saline solution. After 10 minutes we visualized the flap margin with a near-infrared laparoscopic view and we noticed a tracer uptake on the whole edge of the flap, the perforating branches were also evident. The evaluation was repeated at the end of the surgical procedure and we confirmed the good vascularization of the flap (figure 2 ). Results: No early or late post-operative complications were obtained. There was no wound dehiscence, marginal necrosis or surgical site infection. The patient stated satisfaction of the aesthetic level obtained. Conclusion: Verifying the viability of the vulvar flap using near-infrared laparoscopic optics was easy to use, reproducible and extremely economical technique. This could be an extremely useful and reproducible alternative to other more expensive techniques. Disclosure: Nothing to disclose